KOMUNIKASI DAN KHOTBAH: (Suatu Kajian Teologi Komunikasi dalam berkhotbah) - Marlan Hutauruk; Hotliong Verawaty; Dortheys H. E. Fureuw Mandobar (Tepian : Jurnal Misiologi dan Komunikasi Kristen, 2021)
This study aims to describe communication in preaching. In communicating, we can convey what is the intention of the speaker (communicator) to (the communicant), whether it's just to exchange ideas, share information, give advice, invitations and so on. There are many media that can be used as communication, one of which is through preaching, especially for Christians, preaching are the media or means used to convey the Word of God. But in practice, even though the preaching material has been prepared as well as possible, there are many preachers as communicators who cannot provide good communication skills; this is the main problem that hinders communication in preaching. The use of voice and gesture also plays an important role in the preaching, it must be studied because not all people who are born have the ability to communicate, so that God's Word that is delivered does not become bland and can be a blessing for the listeners